Density-oriented public transport corridors: decoding their influence on BRT ridership at station-level and time-slot in Bogotá - Guzman, Luis A.; Gomez, Santiago (Cities, 2021)
This study presents evidence on two factors of the built environment affecting Bus Rapid Transit (BRT) demand at a station level throughout the day. These factors were examined in Bogotá, one of the most densely populated cities in the world, and its BRT system, which operates with high levels of congestion. We proposed an approach to explain how changes in density and mixed activities influence ridership levels. We found that high population and job densities relate to a higher number of BRT boardings in the morning and evening peak hours, respectively. However, these effects decrease in magnitude when both uses are present in the same zone. We found evidence that a balanced mixture of jobs and residences reduces the pressure on BRT boardings. An analysis of the changes during the day and differentiating between working days and weekends indicates that the cause of a balanced ridership lies in the internal capture of job-related trips. We hypothesize that the density and diversity characteristics central to the theory of Transit-Oriented Development (TOD), drive self-containment patterns around public transport catchment areas, alleviating BRT congestion. Using these results, we show how changes in the proposed land-use pattern limits can have different effects on the BRT ridership. Our results underscore the need of incorporating the TOD concept as an instrument for the management of public transport systems in dense and segregated cities and emphasize the importance of achieving a balance between jobs and housing to support less congested high-capacity public transport systems.
Available online 16 December 2020
Gesehen am 30.03.2021